Intraparenchymal hemorrhage from infective endocarditis: A case of double trouble - Farhan Khalid; Anosh Aslam Khan; Hardikkumar Bhanderi; Peter N. Fish; Doantrang Du (IDCases)
Infective Endocarditis is characterized by inflammation of the heart's inner lining and valves which can lead to valve masses made of fibrin, platelets, and the infectious organisms. Patients can present with a wide array of symptoms with neurological symptoms quite rare. Here, we present a case of a 41-year-old who was admitted for IE and later developed an intraparenchymal hemorrhage. A Transesophageal echo (TEE) showed > 2 cm tricuspid valve vegetation and small mitral valve vegetation. After the patient developed confusion an urgent head CT showed a large acute left frontal intra-parenchymal hematoma with intraventricular extension and possible ventricle entrapment. He was treated with emergency decompression hemi-craniotomy and extra ventricular drain placement. A follow-up diagnostic cerebral angiogram revealed a mycotic distal cortical left middle cerebral artery aneurysm for which he underwent Digital Subtraction Angiography (DSA) and embolization of mycotic aneurysm. Neurological complications of IE are rare but life threatening. Early brain imaging is essential for the prompt identification of stroke events, and angiographic evaluation is critical for the diagnosis and management of aneurysms, even when a course of antibiotic therapy is being continued. A timely cardiac surgery to replace vegetative valves is crucial for reducing the adverse events of IE.